1988
DOI: 10.1002/dc.2840040412
|View full text |Cite
|
Sign up to set email alerts
|

Cervical schwannoma with intranuclear vacuoles by fine‐needle sampling without aspiration

Abstract: In a 49-yr-old woman who presented with a cervical mass, a fine-needle specimen without aspiration was suggestive of paraganglioma; there were spindle-shaped cells with pseudoacinar structures and prominent intranuclear vacuoles. Subsequent examination of a mass removed from the vagus nerve clearly identified a schwannoma. The differential diagnosis is discussed, particularly in relation to the presence of intranuclear vacuoles, and it is concluded that this cytological characteristic should not in itself defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Numerous descriptions of the cytologic features of schwannoma exist in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25] . The two largest series of schwannoma aspirations reported to date are a group of 28 cases reported by Dahl et al 26 and 19 cases reported by Resnick et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous descriptions of the cytologic features of schwannoma exist in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25] . The two largest series of schwannoma aspirations reported to date are a group of 28 cases reported by Dahl et al 26 and 19 cases reported by Resnick et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…4 The results of FNA from only 17 other schwannomas appear in the recent literature. [5][6][7][8][9][10][11][12][13][14][15][16][17] Schwannomas are reported to yield cellular aspirates comprising spindle cells arranged singly and in variably sized tissue fragments with a fibrillar ground substance. Some fragments show the spindle cells to be arranged haphazardly, while others display a parallel arrangement, sometimes with nuclear palisading and Verocay body formation.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient schwannomas are reported to show bizarre nuclei without mitotic activity. 4,[8][9][10][11][12][13][15][16][17][18][19] Cell block material and demonstration of S-100 immunoreactivity are reported to be helpful in the diagnosis of schwannoma by aspiration cytology. 9,14 Willems has commented that the aspirates of neurofibromas generally are less cellular than those of schwannomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies allude to the high frequency of nuclear pseudoinclusions (illustrated in Figures 5B and 8C) also being present in these ancient schwannoma cases 15,17,27 . Unfortunately, this atypia has misled some authors to issue false‐positive diagnoses of sarcoma or another neoplasm 11,14,36,37 . Dodd et al.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneous category is dominated by schwannoma which is by far the most common peripheral nerve sheath tumor (PNST), 1 but neurofibroma 2 hybrid PNST, perineurioma, neuroma, dermal nerve sheath myxoma, ganglioneuroma, and granular cell tumor are among the other benign nerve sheath tumors listed by the WHO in this classification. 3,4 Although numerous case reports and small series of fine-needle aspiration (FNA) biopsy cytopathology of benign peripheral nerve tumors (BPNTs) exist, [5][6][7][8][9][10][11][12] only a handful of large series (≥20 cases) are published. [13][14][15][16][17][18][19] We undertook a review of our FNA biopsy experience to assess diagnostic accuracy, role of ancillary studies, and diagnostic traps associated with this category of neoplasms.…”
Section: Introductionmentioning
confidence: 99%